The Effect of Self-Efficacy and Reward on Employee Performance at Bank Nusa Tenggara Timur Head Office Through Work Motivation as a Moderating Variable - Tania Novelen ADOE; Frans GANA; Melkisedek N.B.C. NEOLAKA (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the effect of self-efficacy and reward on employee performance at Bank NTT Head Office, with work motivation as a moderating variable. The main problems discussed include how the relationship between self-efficacy, reward, and motivation to improve employee performance directly and indirectly. The method used is a quantitative approach with an explanatory research type, involving 188 respondents from a population of 354 employees of Bank NTT Head Office. Data collection was carried out through questionnaires and documentation, and analyzed using the Partial Least Square (PLS) technique. The results of the study indicate that self-efficacy, reward, motivation, and employee performance are in the good category. Self-efficacy and reward have a significant direct influence on employee performance, as well as motivation. However, work motivation has not been shown to moderate the influence of self-efficacy and reward on performance. This finding indicates the importance of strengthening psychological aspects and reward systems in supporting employee productivity. The conclusion of this study confirms that direct interventions on self-efficacy and reward are more effective than using motivation as an intermediary variable. Therefore, human resource development should be focused on increasing self-confidence and a fair reward system to optimize organizational performance.